High performance room temperature p-type injection in few-layered tungsten diselenide films from cobalt and palladium contacts. (27th November 2019) - Rastikian, Jacko; Suffit, Stéphan; Timpa, Salvatore; Martin, Pascal; Lafarge, Philippe; Bezencenet, Odile; Della Rocca, Maria Luisa; Barraud, Clément
Abstract: Field-effect electronic devices based on transition metals dichalcogenides (TMDs) have recently received a tremendous interest. Although widely studied, efficient charge injection in those materials is often impeded by the large injection barrier present at the interface between the electrode and the TMD, in particular when holes transport is needed. In this paper, e-beam lithography and e-beam evaporation techniques are used to contact few-layered WSe2 films with patterned metallic electrodes (Co and Pd).. We measured the transport and the injection properties at various gate voltages, source-drain voltages and different temperatures. A quantitative analysis is performed using a two-dimensional version of a thermionic emission model to extract the evolution of the injection barrier height as a function of the gate voltage. Palladium contacts are found to be very transparent in the hole injection regime but weakly tunable under the application of a gate voltage. Cobalt contacts present a low injection barrier which, unlike Pd contacts, can be extremely reduced by electrostatic gating. In both cases low injection barriers with respect to the literature are extracted. These results demonstrate a solid potential for applications implying WSe2 in the hole transport regime. The results reveal also an excellent agreement when compared to previous theoretical studies by taking into account the role of hybridized interfacial states and of the spin–orbit coupling of the contacting material on the injection barrier.